2010
DOI: 10.1016/j.pain.2009.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive sensitization by complement C5a and C3a in mouse

Abstract: Activation of the complement system by injury increases inflammation by producing complement fragments C5a and C3a which are able to recruit and activate immune cells. Complement activation may contribute to pain after inflammation and injury. In the present study, we examined whether C5a and C3a elicit nociception when injected into mouse hind paws in vivo, and whether C5a and C3a activate and/or sensitize mechanosensitive nociceptors when applied on peripheral terminals in vitro. We also examined the dorsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 47 publications
4
65
2
Order By: Relevance
“…Recent evidence showed that C5aR is expressed in primary nociceptive neurons and that C5a could directly sensitize these fibers (12,13). Our studies showed that DF2593A blocked carrageenan and C5a-dependent mechanical hyperalgesia in vivo without sedative or central opioid-like effects.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Recent evidence showed that C5aR is expressed in primary nociceptive neurons and that C5a could directly sensitize these fibers (12,13). Our studies showed that DF2593A blocked carrageenan and C5a-dependent mechanical hyperalgesia in vivo without sedative or central opioid-like effects.…”
Section: Discussionsupporting
confidence: 59%
“…For example, C5a was produced at the inflammatory sites and elicited mechanical hyperalgesia by activating the C5aR on infiltrated PMN (7). Direct intraplantar injection of C5a in mice elicited both heat and mechanical hyperalgesia by sensitizing primary afferent C-nociceptors (12,13). Local activation of C5aR has been also implicated in the pathogenesis of postsurgical pain, a model of postoperative pain (13).…”
mentioning
confidence: 99%
“…Based on these experiments we postulated that fracture can induce the regional expression of novel antigens in the fracture limb hindpaw skin and sciatic nerve, subsequently triggering B cells to secret autoantibodies capable of binding to those antigens and initiating a regionally restricted antibody-antigen-complement response resulting in complement sensitization of nociceptive neurons [23]. The current study tested the hypothesis that serum antibodies from fracture mice can induce regionally restricted pain behaviors in B cell deficient fracture mice and proceeded to identify the immunoglobulin isotype responsible for these pronociceptive effects.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of nociceptors is achieved by substances that interact with receptors and/or ion channels, leading to changes on the excitability of primary and central sensorial neurons and the induction of nociception in response to a stimulus [78]. Inflammatory mediators such as cytokines and chemokines (TNF-α, IL-1 and IL-8) [20], bradykinin [29,74], complement factors C3a and C5a [40], prostaglandins [28] and leukotrienes [18], sympathomimetic amines [30], PAF, histamine and serotonin [11] are released at the site of inflammation and act on specific receptors and/or ion channels present in the peripheral terminals of nerve fibers, causing sensitization [17,77]. These mediators are released by inflammatory cells, including mast cells [3].…”
Section: Introductionmentioning
confidence: 99%